Beyond inclusion and exclusion : Jewish experiences of the First World War in Central Europe - Crouthamel, Jason; Geheran, Michael, 1971-; Grady, Tim (Timothy L.); Köhne, Julia (Berghahn Books, 2019)
"During the First World War, the Jewish population of Central Europe was politically, socially, and experientially diverse, to an extent that resists containment within a simple historical narrative. While antisemitism and Jewish disillusionment have dominated many previous studies of the topic, this collection aims to recapture the multifariousness of Central European Jewish life in the experiences of soldiers and civilians alike during the First World War. Here, scholars from multiple disciplines explore rare sources and employ innovative methods to illuminate four interconnected themes: minorities and the meaning of military service, Jewish-Gentile relations, cultural legacies of the war, and memory politics"--